1994
DOI: 10.1159/000201139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 7 Years’ Daily Oral Administration of Omeprazole to Beagle Dogs

Abstract: Ten beagle dogs were given omeprazole orally at a dose of 0.17 mg/kg (0.5 μmol/kg) daily for 7 years. Six dogs served as controls. Regularly evaluated criteria were clinical signs, body weight, food consumption, rectal temperature, electrocardiography, hematology, blood chemistry, urinalysis, ophthalmoscopy, gastroscopic examination including gastric mucosal biopsy sampling for histological evaluation, pharmacokinetics of omeprazole, and plasma gastrin levels. After approximately 5 years, a quantitative gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 15 publications
1
7
0
Order By: Relevance
“…No complications or side effects related with the administration of omeprazole were noticed. This is consistent with the long‐term observation in dogs administered 0.17 mg/kg oral omeprazole which showed no adverse clinical effects even after 7 years of treatment (Safholm and others 1994).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…No complications or side effects related with the administration of omeprazole were noticed. This is consistent with the long‐term observation in dogs administered 0.17 mg/kg oral omeprazole which showed no adverse clinical effects even after 7 years of treatment (Safholm and others 1994).…”
Section: Discussionsupporting
confidence: 91%
“…In human beings, omeprazole should ideally be administered twice before anaesthesia to reach effective plasma concentrations (Escolano and others 1992). In dog, peak plasma concentration of omeprazole has been found to occur within 2 h of dosing (Safholm and others 1994) and the antisecretory effect to last up to 4 days after a single maximal dose (Larsson and others 1985), without adverse clinical signs (Safholm and others 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Nausea, abdominal pain, constipation, flatulence and diarrhea are common side effects in humans (1.5-3% of patients for omeprazole), but most of these effects are not observed in animals (Kaya, 2007;Papich, 2009;Wallacei and Sharkey, 2011). Säfholm et al (1994) orally administered at a dose of 0.17 mg kg −1 to Beagle dogs and a detailed clinical and gastroscopic examination including gastric mucosal biopsy were regularly performed for 7 years. It was concluded that 7 years' treatment with omeprazole in dogs, in a dose resulting in clinically relevant plasma concentrations, did not cause any adverse effects in any of the animals.…”
Section: Adverse Effects and Drug Interactionsmentioning
confidence: 99%
“…The effects of long-term administration of acid inhibitors has not been studied in the Norwegian Lundehund, but beagle dogs have been given omeprazole daily for 7 years [73]. There were no changes in the gastric mucosa at termination including ECL cell numbers, but the dogs receiving omeprazole had similar fasting and meal-stimulated plasma gastrin levels compared to controls which means the dogs had not received an adequate dose of PPI.…”
Section: Animal Modelsmentioning
confidence: 99%